Rapid Isolation and Multiplexed Detection of Exosome Tumor Markers Via Queued Beads Combined with Quantum Dots in a Microarray - Bai, Yanan; Lu, Yunxing; Wang, Kun; Cheng, Zule; Qu, Youlan; Qiu, Shihui; Zhou, Lin; Wu, Zhenhua; Liu, Huiying; Zhao, Jianlong; Mao, Hongju (Nano-Micro Letters, 2019)
Tumor-derived exosomes are actively involved in cancer progression and metastasis and have emerged as a promising marker for cancer diagnosis in liquid biopsy. Because of their nanoscale size, complex biogenesis, and methodological limitations related to exosome isolation and detection, advancements in their analysis remain slow. Microfluidic technology offers a better analytic approach compared with conventional methods. Here, we developed a bead-based microarray for exosome isolation and multiplexed tumor marker detection. Using this method, exosomes are isolated by binding to antibodies on the bead surface, and tumor markers on the exosomes are detected through quantum dot (QD) probes. The beads are then uniformly trapped and queued among micropillars in the chip. This design benefits fluorescence observation by dispersing the signals into every single bead, thereby avoiding optical interference and enabling more accurate test results. We analyzed exosomes in the cell culture supernatant of lung cancer and endothelial cell lines, and different lung cancer markers labeled with three QD probes were used to conduct multiplexed detection of exosome surface protein markers. Lung cancer-derived samples showed much higher (~ sixfold–tenfold) fluorescence intensity than endothelial cell samples, and different types of lung cancer samples showed distinctive marker expression levels. Additionally, using the chip to detect clinical plasma samples from cancer patients showed good diagnostic power and revealed a well consistency with conventional tests for serological markers. These results provide insight into a promising method for exosome tumor marker detection and early-stage cancer diagnosis. Highlights: 1 A bead-based microarray for exosome isolation and multiplexed tumor marker detection was developed. 2 The beads are uniformly trapped and queued among the micropillars in the chip, which can avoid optical interference and enable more accurate test results. 3 The results with different types of lung cancer exosome samples showed distinctive marker expression levels.